The Racially Unequal Impacts of Disasters and Federal Recovery Assistance on Local Self-Employment Rates. (April 2022) - Bento, Asia; Elliott, James R.
This study examines racial inequalities in changing self-employment rates associated with natural hazard impacts and federal recovery assistance in ethnoracially diverse metropolitan counties between 2000 and 2010. It advances the viewpoint that such inequalities can stem from hoarded opportunities tied to white privilege in addition to commonly highlighted social vulnerabilities tied to racial inequities and exclusion. To test that proposition, we conduct change-score analyses using county-level data from the US Census Bureau, the Spatial Hazard Events and Losses Database for the United States, and the Federal Emergency Management Agency. Results indicate that (a) overall, self-employment rates increase with local property damages from natural hazards, especially among white and Latino workers; (b) those increases are largely explained by the amount of federal public assistance received for disaster recovery, not property damages themselves; and (c) white workers experience the most positive and consistent increases in self-employment from federal recovery assistance. Implications for understanding racial inequities stemming from current and future disasters and government assistance are discussed.